A community development approach to service‐learning: Building social capital between rural youth and adults1. Issue 138 (22nd July 2013) - Henness, Steven A.; Ball, Anna L.; Moncheski, MaryJo
Abstract: Using 4‐H and FFA case study findings, this article explores how community service‐learning supports the building of social capital between rural youth and adults and the positive effects on community viability. Key elements of practice form a community development approach to service‐learning, which opens up doorways for youth to partner with adult leaders and decision makers, gain credibility as resources and problem solvers, address community issues, and raise awareness of the value of school‐ and community‐based youth programs. Case study evidence suggests that rural 4‐H and FFA youth and adults benefit from the bonding relationships they form through working together to solve community issues over time. Positive community outcomes are noted as well, including increased community capacity and community recognition. By focusing on social capital as a key outcome of community service‐learning, 4‐H youth and community development extension professionals, educators, and other practitioners have contributed to the viability of rural communities.